Cashless Mobile Financial Services: Rapid growing financial sector in Bangladesh's Financial Industry - Moutusi Tanha; Md. Ruhul Amin; Md. Yeamin Masum; Mithun Bairagi; Md. Habibur Rahman; Md. Zahid Hasan (Annals of Management and Organization Research, 2024)
Purpose: Mobile finance services have grown in Bangladesh, reaching a large population without access to traditional banks. This research investigates how mobile banking affects Bangladesh's economy. The paper analyzes mobile financial services in the nation and identifies growth prospects. Furthermore, the study will examine the potential impact of mobile financial services on improving the quality of life for low-income persons and their role in combating poverty. Methodology/approach: In order to gather data on the adoption and utilization of mobile financial services in Bangladesh, the research will integrate primary and secondary sources, such as surveys, interviews, and case studies. The study will also examine the socioeconomic and demographic factors influencing the country's adoption of mobile financial services. Results/findings: The study also analyzed mobile financial services' economic benefits and potential drawbacks. The study will focus on the potential impact of mobile finance services on enhancing financial inclusion, expanding access to credit, and promoting economic growth in Bangladesh. The thesis will examine the potential impact of mobile financial services on enhancing financial literacy among the population and boosting the nation's GDP. Limitations: Bangladesh's Information and Communication (ICT) strategy highlights the government's digital initiatives and policy goals as weak regarding digital inclusion. Consequently, the extent to which digital services and financial technology (fintech) will provide financial inclusion in rural Bangladesh remains uncertain. To achieve financial inclusion in the digital economy through digital services, rural populations must have access to digital equipment and supportive social contexts. Contribution: The research will investigate Bangladesh's mobile banking regulatory system and suggest improvements to protect consumers. It will also examine mobile financial service providers' problems and opportunities, as well as solutions. This article seeks to study mobile banking services in Bangladesh and find development opportunities. The findings will inform policymakers, financial institutions, and service providers in Bangladesh and other developing nations where mobile banking proliferates. Keywords: Cashless, Mobile Banking, Mobile Financing